Analisis Risiko Kinerja Keuangan PT. Asuransi ‘X’ pada Periode COVID-19 dengan Menggunakan Metode Altman Z-Score - Timothy Victory Tewu (Journal on Education, 2022)
The Insurance Industry as part of the Non-Bank Financial Institutions in Indonesia, plays an important role in increasing Indonesia's economic growth, therefore it is only natural that it receives the support and attention of all parties. The insurance industry is increasingly playing a role in the welfare of the Indonesian economy, because it provides many benefits both individually, society and the country's economy, according to the general opinion that is developing in society. In this paper, researchers want to analyze the risk level of the financial performance of PT. Insurance 'X'. During the Covid-19 period 2020-2022. The data used in this study is secondary data in the form of the company's annual financial reports obtained from IDX Indonesia Stock Exchange (IDX). Data analysis was performed using discriminant analysis (Z-Score) developed by Altman. The sample used is financial data from PT. Insurance 'X'. Years 2020-2022. From the results of data analysis it is known that the level of financial performance risk of PT. Insurance 'X'. In 2020 - 2022 it is in the very high risk category because it has a Z-Score value below 1.80. Using the results of discriminant analysis (Z-Score) which shows that PT. Insurance 'X' is in a very high risk position and if business management is not carried out properly it can cause long-term bankruptcy or bankruptcy for the general insurance company. Improvements will occur in 2021 where the Z-Score value of PT. Insurance 'X'. experienced a significant increase to = 1.81 even though the resulting risk is still high, this indicates that the condition of financial performance is still at a critical point or high risk, because this position indicates that management is still obliged to improve financial performance until the Z-Score is in a position safe or >3.